KEANEKARAGAMAN JENIS TUMBUHAN DAN PENDUGAAN CADANGAN KARBON DI ATAS PERMUKAAN TANAH DI KAWASAN HUTAN BUKIT BARISAN BAGIAN BARAT KOTA PADANG - Yastori, .; Chairul, .; Syamsuardi, .; Mansyurdin, .; Maideliza, Tesri (Metamorfosa: Journal of Biological Sciences; Vol 3 No 2 (2016)DO - 10.24843/metamorfosa.2016.v03.i02.p02, 2016)
Indonesia has a vast forest area. The extent of Indonesia's forests is one of the natural resources are prone to damage due to human interests in meeting their needs. One of the damage that often occurs when current is forest fires. Forest destruction accounts for 20-25% of global CO 2 emissions that contribute to climate change or global warming. Unspoiled forest with a diversity of plant species are long-lived and litter is a place to store a lot of carbon stocks (C) the highest. The aim of this study was to determine the diversity of plants and the amount of carbon stock above ground level in the forests of the Bukit Barisan of Padang, West Sumatra. Tree biomass was calculated on a plot of 20x20 m, 10x10 m pole, stake 5x5 m, for counting down plant biomass and litter on the plot with a size of 2x2 m (National Standardization Agency, 2011). Biomass calculated by the Ketterings et al . formula (2001). In Bukit Barisan Forest Area, West Sumatra, derived carbon content was 16.029,70 ton/ha. Diversity type was highest at tree level on Station 1, classified as very high diversty with diversity index (H’) 3.10.
Keywords: forest, carbon, biomass, diversity, diversity index